Association Between Room Location and Adverse Outcomes in Hospitalized Patients. (April 2019) - Mayampurath, Anoop; Ward, Christopher; Fahrenbach, John; LaFond, Cynthia; Howell, Michael; Churpek, Matthew M.
Objective: To investigate whether a patient's proximity to the nurse's station or ward entrance at time of admission was associated with increased risk of adverse outcomes. Method: We conducted a retrospective cohort study of consecutive adult inpatients to 13 medical–surgical wards at an academic hospital from 2009 to 2013. Proximity of admission room to the nurse's station and to the ward entrance was measured using Euclidean distances. Outcomes of interest include development of critical illness (defined as cardiac arrests or transfer to an intensive care unit), inhospital mortality, and increase in length of stay (LOS). Results: Of the 83, 635 admissions, 4, 129 developed critical illness and 1, 316 died. The median LOS was 3 days. After adjusting for admission severity of illness, ward, shift, and year, we found no relationship between proximity at admission to nurse's station our outcomes. However, patients admitted to end of the ward had higher risk of developing critical illness (odds ratio [ OR ] = 1.15, 95% confidence interval [CI] = [1.08, 1.23]), mortality ( OR = 1.16, 95% CI [1.03, 1.33]), and a higher LOS (13-hr increase, 95% CI [10, 15] hours) compared to patients admitted closer to the ward entrance. Similar results were observed in sensitivity analyses adjusting for isolation room patients and considering patients without room transfers in the first 48 hr. Conclusions: Our study suggests that being away from the nurse's station did not increase the risk of these adverse events in ward patients, but being farther from the ward entrance was associated with increase in risk of adverse outcomes. Patient safety can be improved by recognizing this additional risk factor.